Analysis of Cheerful Gymnastics Activities in Developing the Gross Motor Skills of Early Childhood at Al Fitrah Kindergarten, Jambi - Ratumas Sinta Naila (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Physical-motor ability is a developmental aspect that requires stimulation from an early age. One initiative undertaken by TK Al Fitrah Jambi is the implementation of